Implementation of an OBE-based multicultural curriculum in higher education: A case study at UIN Sunan Kalijaga - Humaira Silfiani; Sukiman Sukiman (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2025)
This study examines the implementation of a multicultural curriculum integrated within an Outcome-Based Education (OBE) framework in higher education. While previous studies have explored OBE and multicultural education separately, limited research has addressed their integration in Islamic higher education contexts. This study aims to analyze the implementation, benefits, and challenges of an OBE-based multicultural curriculum at UIN Sunan Kalijaga, Indonesia. A qualitative approach was employed using semi-structured interviews, observations, and document analysis. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings indicate that the integration of multicultural values into the OBE framework enhances graduate competencies by aligning academic, social, and spiritual dimensions. The curriculum is characterized by the integration of unity of sciences, Islamic moderation, and green campus principles. However, the implementation faces challenges such as limited resources, lecturer readiness, and the complexity of outcome-based assessment. This study contributes to the literature by providing empirical insights into how multicultural education can be systematically integrated within an OBE framework to support the development of adaptive, value-based graduates in higher education.